Actividad antibacteriana de las familias vegetales Lamiaceae y Myrtaceae en la cavidad oral. Una revisión narrativa. - Delgado del Castillo, Javier Enrique (Universidad Antonio Nariño, 2021)
In this narrative review, 19,441 publications were consulted in different databases, of which 707 articles were consistent with the objectives set. These selected articles were screened according to the inclusion and exclusion criteria, to finally choose a total of 24 articles. Similarly, from these 24 articles, their eligibility was determined, obtaining 4 articles that were included in this Narrative Review.